(untitled) (Teología, 2020)
The authors return once again to the question about the interdisciplinary dialogue between theology and literature through an interview with Lucio Gera, who has given a significant impulse to this particular research. In this oportunity, biographical aspects relating to the interdisciplinary method of theological dialogue with the classics and theater and the place of literature in theology are examined. These questions open the horizons to new ideas along these latitudes.